Regulating Standard form of consumer contracts: The legal treatment of selected asian jutisdictions - Azimon Abdul Aziz,; Sakina Shaik Ahmad Yusoff, (2010)
The use of standard form contract is extensively widespread in the era of globalisation. It has now become a predominant feature of many consumer contracts. Although initially it was formed as an agent to facilitate market transactions, it is now seen as hindering the business process and increasing the cost of goods. Its practice in the daily consumer transaction has drawn attention due to its nature and characteristics.Forms contract are not a result of a negotiation process; they are offered on a ‘ take it or leave it’ basis, they do not require meeting of mind and they are usuallynot read by consumers. Its contents often consist of unfair terms and exclusion clauses which often give benefits and advantage to the one who prepares the contract. In this new era, the practice of standard form contract reflects a new dimension of oppression of the consumers. It has further eroded the protection of consumers in many commercial transactions. Hence this paper aims at exploring comparatively the legal treatment on standard form contract in the context of consumer trade in selected Asian jurisdictions, namely Malaysia, Israel, Thailand and Peoples Republic of China